Design and Simulation of Ground Station (GS) Television Channel (TV CH) Group (University of Khartoum Engineering Journal, 2021)
The Multiple Channel per Carrier (MCPC) is considered an efficient alternative when used in Ground Station (GS) TV channel stations as it accommodate multiple channel on a limited frequency range. The MCPC technique has been widely used worldwide due to its efficiency. The MCPC technique offers exemplary performance over the traditionally Single channel Per Carrier (SCPC) when considering system accuracy, time, and cost. In this study, the MCPC static mode technique has been investigated using MATLAB tool to simulate a four TV CH system. The GS transmitter and receiver components referenced to four explicit points representing the number of channels carried by the satellite. These components have been constructed and observed using Spectrum Analyzer.